A hybrid implant combining a macroporous device with immunoprotective microcapsules for cell therapy applications: A conceptual in vitro study - Adam Stell; Vijayaganapathy Vaithilingam; Sami G. Mohammed; Rick H.W. de Vries; Denise F.A. de Bont; Eelco J.P. de Koning; Aart A. van Apeldoorn (Materials Today Bio)
Cell encapsulation strategies including macro- and micro-delivery devices have been widely used in cell therapy due to their ability to provide immunoprotection to the transplanted cells. While both strategies can provide mechanical and physiochemical support for maintaining cell survival and function, they each have their limitations. In this study, we report the design and fabrication of a hybrid implant combining the advantages of both macro- and micro-cell delivery devices. The hybrid implant comprises a microwell-array macroporous device fabricated from non-degradable clinically approved polyvinylidene fluoride (PVDF) combined with immunoprotective alginate microcapsules. The microwell design provides a vessel to retain individual microcapsules, while the pores enable unhindered mass transport of nutrients and oxygen to the encapsulated cells and support vascular ingrowth. We show that both rodent pseudoislets and primary human islets maintain their viability and function inside the hybrid implant in a proof-of-concept study. Mechanically, it is strong and flexible suitable for surgical handling and for eventual retrieval for replacement. The hybrid implant also supports the growth of human umbilical vein endothelial cells (HUVEC) across its surface allowing in vitro “prevascularization”, which can potentially accelerate blood vessel formation in poorly vascularized transplantation sites such as the subcutaneous space. In conclusion, the hybrid cell delivery device, which confers immunoprotection and allows prevascularization, can act as a protective container during surgical handling and retrieval of microencapsulated cells opening a wide range of cell therapy applications including stem cells.